Preclinical Evaluation of HER2-Targeting DARPin G3: Impact of Albumin-Binding Domain (ABD) Fusion - Deev S. M. Sergey Mikhaylovich; Oroujeni M. Maryam; Garousi J. Javad; Gräslund T. Torbjörn; Li R. Ruonan; Rosly A. H. B. Alia Hani Binti; Orlova A. M. Anna Markovna; Konovalova E. V. Elena Valerjevna; Shulga (Schulga) A. A. Aleksey Anatolievich; Vorobjeva (Vorobyeva) A. G. Anzhelika Grigorjevna; Tolmachev V. M. Vladimir Maksimilianovich (2024, 2024)
Title screen